2010
DOI: 10.1016/j.vetpar.2009.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Eucalyptus spp. essential oils and their insecticidal effects on Lutzomyia longipalpis

Abstract: The chemical composition of essential oils from three species of plants belonging to the Eucalyptus genus was determined and, their insecticidal effects on egg, larva and adult phases of Lutzomyia longipalpis were assessed. The insects were collected in the municipality of Sobral in the State of Ceará, Brazil. Five treatments with different concentrations were performed along with two negative controls, distilled water and Tween 80 (3%), and a positive control, cypermethrin (0.196mg/ml). The tests were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 26 publications
8
100
1
3
Order By: Relevance
“…Similar results were obtained with the Eucalyptus sp. oils on eggs, larvae and adults of Lutzomyia longipalpis (Maciel et al, 2010). Our results can explain the effectiveness of essential oils on the three biological stages of E. ceratoniae.…”
Section: Biological Activities Of Essential Oils Against E Ceratoniaesupporting
confidence: 55%
“…Similar results were obtained with the Eucalyptus sp. oils on eggs, larvae and adults of Lutzomyia longipalpis (Maciel et al, 2010). Our results can explain the effectiveness of essential oils on the three biological stages of E. ceratoniae.…”
Section: Biological Activities Of Essential Oils Against E Ceratoniaesupporting
confidence: 55%
“…Furthermore, Younis et al (14) reported that small dense LDL, which is particularly associated with the development of coronary heart disease (CHD), is preferentially glycated in non-diabetic human serum. Cineole is also known as eucalyptol, the major oil component of eucalyptus (15). Although cineole was detected in a hydrophilic extract, it is a water-insoluble and colorless liquid with a camphor-like odor with a spicy and cooling taste (16).…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptol was also found in majority of other species of Eucalyptus, such as E. staigeriana (Gilles et al, 2010), E. globules (Maciel et al, 2010;Tyagi and Malik, 2011) and E. urophylla (Cheng et al, 2009). Nevertheless, the main component in other species of Eucalyptus can be a different compound, such as piperitone (E. dives), (E)-methyl cinnamate (E. olida) (Gilles et al, 2010), α-pinene (E. camaldulensis) (Cheng et al, 2009), limonene (E. staigeriana), β-citronellal (E. citriodora) (Maciel et al, 2010), or p-cymene (E. tereticorni) (Toloza et al, 2006). The chemical composition of essential oil is affected by several factors, such as species, geographical location, harvest time, plant part and isolation method (Cimanga et al, 2002;Penalver et al, 2005;Marzoug et al, 2011).…”
Section: Discussionmentioning
confidence: 89%